2023
DOI: 10.1021/acs.molpharmaceut.3c00224
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Targeted Therapies for Colorectal Cancer Treatment

Elodie Péraudeau,
Brigitte Renoux,
Sheik Emambux
et al.

Abstract: The design of innovative therapeutic strategies enabling the selective destruction of tumor cells while sparing healthy tissues remains highly challenging in cancer therapy. Here, we show that the combination of two targeted therapies, including bevacizumab (Bev), and a β-glucuronidase-responsive albumin-binding prodrug of monomethyl auristatin E (MMAE), is efficient for the treatment of colorectal cancer implanted in mice. This combined therapy produces a therapeutic activity superior to that of the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The Cell Counting Kit-8 (CCK-8) (Solarbio, Beijing, China) assay was employed to assess the in vitro cytotoxicity of the MLSV system. In brief, HEK 293T cells were incubated in 96-well plates at a density of 5 × 10 3 cells overnight. Various concentrations of MLSV and DMP were added, with PEI25K used as the standard control for 24 h. Then, the CCK-8 agent was added to the cells to detect cytotoxicity at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The Cell Counting Kit-8 (CCK-8) (Solarbio, Beijing, China) assay was employed to assess the in vitro cytotoxicity of the MLSV system. In brief, HEK 293T cells were incubated in 96-well plates at a density of 5 × 10 3 cells overnight. Various concentrations of MLSV and DMP were added, with PEI25K used as the standard control for 24 h. Then, the CCK-8 agent was added to the cells to detect cytotoxicity at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, immunotherapy targeting immune checkpoints such as PD-1/PD-L1 axis and CTLA-4 shows promise in treating advanced CRC, particularly in CRC tumors with microsatellite instability-high (MSI-H) or deficient mismatch repair (dMMR)[ 22 ]. Combination therapies, involving immunotherapy with chemotherapy, targeted therapies, and other immunomodulators, further offer the potential of synergistic effects and enhanced treatment efficacy[ 23 , 24 ]. Ongoing research efforts on predictive biomarkers, such as tumor mutational burden (TMB) and immune cell infiltration patterns, aim to identify patients most likely to benefit from immunotherapy[ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is characterized by its poor diagnosis, high metastases, and mortality 1 . In recent decades, several newly developed strategies, including targeted therapy and CAR‐T cell‐based immunotherapy, were developed 2,3 . Recent efforts also suggested that mechanical stimuli‐driven cancer therapy can provide a direct therapeutic effect or a mediator to augment traditional cancer therapy 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent decades, several newly developed strategies, including targeted therapy and CAR-T cell-based immunotherapy, were developed. 2,3 Recent efforts also suggested that mechanical stimuli-driven cancer therapy can provide a direct therapeutic effect or a mediator to augment traditional cancer therapy. 4,5 In general, shear flow is essential for maintaining physiologies and lifespan of endothelial cells (ECs), the regulatory effects of shear flow on circulating tumor cells (CTCs) were also reported.…”
Section: Introductionmentioning
confidence: 99%